First experimental evidence suggests use of glucobrassicin as source of auxin in drought-stressed Arabidopsis thaliana - Hornbacher, Johann; Horst-Niessen, Ina; Herrfurth, Cornelia; Feussner, Ivo; Papenbrock, Jutta (Frontiers in Plant Science, 2022)
The synthesis of indole-3-acetonitrile (IAN) from the indolic glucosinolate (iGSL) glucobrassicin (GB) is a unique trait of members of the Brassicales. To assess the contribution of this pathway to indole-3-acetic acid (IAA) synthesis under stress conditions, drought stress (DS) experiments with Arabidopsis thaliana were performed in vitro. Analysis of GSLs in DS plants revealed higher contents of GB in shoots and roots compared to control plants. Deuterium incorporation experiments showed the highest turnover of GB compared to all other GSLs during drought conditions. Evidence suggests the involvement of the thioglucosidase BGLU18 in the degradation of GB. The nitrile specifier proteins NSP1 and NSP5 are known to direct the GSL hydrolysis towards formation of IAN. Nitrilases like NIT2 are able to subsequently synthesize IAA from IAN. Expression of BGLU18, NSP1, NSP5 and NIT2 and contents of GB, IAN and IAA were significantly elevated in DS plants compared to control plants. suggesting the increased use of GB as IAA source. Significantly higher contents of reactive oxygen species in DS bglu18 and epithionitrile specifier protein (esp) mutants compared to Col-0 indicate higher stress levels in these mutants highlighting the need for both proteins in DS plants. Furthermore, GB accumulation in leaves was higher in both mutants during DS when compared to Col-0 indicating enhanced synthesis of GB due to a lack of breakdown products. This work provides the first evidence for the breakdown of iGSLs to IAN which seems to be used for synthesis of IAA in DS A. thaliana plants.